Characterization of phthalates exposure and risk for cosmetics and perfume sales clerks. (February 2018) - Huang, Po-Chin; Liao, Kai-Wei; Chang, Jung-Wei; Chan, Shiou-Hui; Lee, Ching-Chang
Abstract: High levels of phthalates in name-brand cosmetics products have raised concerns about phthalate exposure and the associated risk for cosmetics sales clerks. We assessed the exposure and risk of phthalates in 23 cosmetics, 4 perfume, and 9 clothing department store sales clerks. We collected 108 urine samples pre- and post-shift and analyzed for phthalate monoesters through liquid chromatography–electrospray ionization–tandem mass spectrometry. Phthalates in 32 air samples were collected and analyzed through gas chromatography–mass spectrometry. Demographic characteristics and information on the exposure scenarios were obtained through questionnaires. Principal component analysis, cluster and risk analysis were applied to identify the exposure profile and risk of phthalate. Median post-shift levels of urinary mono-2-ethylhexyl phthalate (MEHP) and monomethyl phthalate (MMP) were significantly higher than the corresponding pre-shift levels in cosmetics group (53.3 vs. 30.9 μg/g-c for MEHP; 34.4 vs. 22.5 μg/g-c for MMP; both P < 0.05) and the post-shift levels of urinary MMP was significantly higher than the corresponding pre-shift levels in perfume group (26.6 vs. 14.9 μg/g-c, P < 0.05). Median levels of air diethyl phthalate (DEP) in cosmetics (1.77 μg/m 3 ) and perfume (1.75 μg/m 3 ) groups and di-(2-ethylhexyl) phthalate (DEHP) in perfume group (6.98 μg/m 3 ) were higher than those in clothing group (DEP: 0.89; DEHP: 2.16 μg/m 3 ). Over half of cosmetic (70%) and perfume sale clerks had exceeded cumulative risk of phthalate exposure for anti-androgenic effect. We concluded that cosmetic and perfume workers had increased risks of reproductive or hepatic effects for DBP and DEHP exposure. We suggest that not only inhalation but dermal exposure is important route of phthalate exposure for cosmetics and perfume workers. Graphical abstract: Image 1 Highlights: Cosmetics and perfume sales clerks had higher levels of urinary MEP, MBP and MEHP. Higher levels of air DEP and DEHP were measured in cosmetics and perfume sales regions. Increased and exceeded risk of phthalate exposure in cosmetic workers should be concerned especially for DBP, DEP, and DEHP. Inhalation and cosmetics use on skin could be critical routes of phthalate exposure in cosmetics and perfume sales clerks. Abstract : Increased Risk for Phthalate Exposure in Cosmetic and Perfume Sales Clarks.